Analysis method for anisotropic heat transport characteristics of suspended-state WTe2 film
By analyzing the anisotropic heat transport characteristics of suspended WTe2 films, the problem of local hot spot accumulation in integrated circuits is solved, and guidance on device structure design and performance optimization is provided, which extends the service life of the device.
Patent Information
- Application Number
- CN202411689337.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The prior art is difficult to effectively manage the accumulation of local hot spots in integrated circuits due to insufficient thermal performance regulation of materials, affecting device life.
By analyzing the anisotropic heat transport characteristics of suspended WTe2 films, including determining their lattice orientation, performing Raman spectroscopy tests to calculate first-order temperature coefficient and power coefficient, and computing the absorption rate test to calculate in-plane thermal conductivity and heat transfer. The anisotropy ratio.
It provides valuable guidance on the structural design, performance optimization and heat dissipation regulation of WTe2 functional devices, extending the service life of the device.
Smart Images

Figure CN119470553A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of application of two-dimensional materials, and in particular to a method for analyzing anisotropic thermal transport characteristics of a suspended WTe2 film. Background Art
[0002] Tungsten ditelluride (WTe2) is an anisotropic two-dimensional material with a low symmetry in the lattice structure. Compared with isotropic two-dimensional materials with a high symmetry in the lattice structure, anisotropic two-dimensional materials have more diverse thermal, mechanical, electrical and other physical properties within the plane. Figure 1 The figure shows the low-symmetry lattice structure of tungsten ditelluride (WTe2): the W-Te-W atomic layers are stacked vertically along the z-axis through van der Waals forces to show a square lattice. The W atoms form WW chains along the x-axis, and the upper Te atomic layer is rotated 180° relative to the lower Te atomic layer, showing an obvious anisotropic structure. The x-axis is defined as the zigzag direction, and the y-axis is defined as the armchair direction.
[0003] Compared with isotropic materials, anisotropic two-dimensional materials can provide new degrees of freedom for the structural design, physical property regulation and directional application exploration of electronic devices. Tungsten ditelluride (WTe2) is one of the low-symmetry two-dimensional materials that has received more attention in recent years. This material has the advantages of large atomic mass, low Debye temperature, unsaturated giant magnetoresistance and superconducting properties, thus having a wide range of application prospects for functional devices. For anisotropic two-dimensional materials, the low-symmetry lattice structure makes the phonon scattering of the material have directional differences, thus showing anisotropic heat transport properties. Two-dimensional materials with thermal anisotropy can make the heat generated by devices based on anisotropic two-dimensional materials during operation preferentially dissipate along the direction of high thermal conductivity. With the development of devices, the size of transistors has gradually become smaller, and the integration density has gradually increased. A substantial increase in power consumption per unit area will form local hot spots inside the device. When heat accumulation is severe, it may damage the circuit and affect the device life. Therefore, how to effectively manage the device thermally to avoid heat accumulation is very important for the structural design and performance optimization of actual devices.
[0004] Based on this problem, the thermal properties of materials need to be explored and regulated in the design of modern integrated circuits. Among the many excellent physical properties of anisotropic two-dimensional materials, understanding the anisotropic thermal transport properties will be conducive to effective thermal management of devices and thus extend the service life of devices, and can provide valuable guidance for the structural design and performance optimization of WTe2 devices. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the problems of the prior art, the present invention provides an analysis method for the anisotropic thermal transport properties of suspended WTe2 thin films. By analyzing the anisotropic thermal transport properties of suspended WTe2, reference and guidance can be provided for the structural design, performance optimization and regulation and management of thermal dissipation of WTe2 functional devices.
[0007] (II) Technical solution
[0008] A method for analyzing anisotropic thermal transport properties of a suspended WTe2 film, comprising:
[0009] S1, providing a suspended WTe2 film; the suspended WTe2 film is a structure formed by the WTe2 film covering the hole area on the silicon substrate;
[0010] S2, determine the lattice orientation of the suspended WTe2 film;
[0011] S3. Test the Raman spectrum along the zigzag direction and armchair direction of the suspended WTe2 film at different temperatures and different laser powers, analyze the variation of the Raman characteristic peak frequency with temperature and laser power, and substitute the corresponding relationship formula I and formula II to calculate the first-order temperature coefficient χT and the first-order power coefficient χP of the suspended WTe2 film along the zigzag direction and armchair direction respectively;
[0012] Among them, the relationship between the Raman characteristic peak frequency and temperature is as follows:
[0013] ω=ω0+χ T T Formula I
[0014] Where ω0 is the Raman characteristic peak frequency of the sample at 0K, T is the actual temperature at that time, and χ T The corresponding first-order temperature coefficient is the relationship between the material Raman characteristic peak frequency and temperature;
[0015] The linear relationship between Raman characteristic peak frequency and power is as follows:
[0016] Δω=ω(P2)-ω(P1)=χ P( P2-P1) = x P ΔP Formula II
[0017] Where P is the laser power, Δω is the change in Raman characteristic peak frequency caused by the power increasing from P1 to P2, and χ P It is the first-order power coefficient, i.e. the relationship between the Raman characteristic frequency and power of the material;
[0018] S4. The absorbance of the test sample along the zigzag direction and the armchair direction at the excitation laser wavelength is calculated according to formula III based on the sample thickness h and the in-plane thermal conductivity and thermal transport anisotropy ratio of the suspended WTe2 film along the zigzag direction and the armchair direction;
[0019] The in-plane thermal conductivity κ of the suspended WTe2 thin film sample is calculated as follows:
[0020] κ=χ T (1 / 2πh)(δω / δP A ) -1 Formula III;
[0021] Thermal transport anisotropy ratio = κ zigzag / κa rmchair ;
[0022] Where h is the thickness of the sample, δω is the absorption of δP by the sample. A The change in the characteristic peak frequency after the power is A is the absorbed power of the sample, P A =A×P, P is the laser power, and A is the absorbance value of the sample at the test laser wavelength.
[0023] According to a preferred embodiment of the present invention, in S1, the method for preparing the suspended WTe2 film is:
[0024] S11. Take a clean glass slide and wipe it with alcohol, cut a piece of PDMS and stick it on the glass slide for later use; cut a clean tape, use tweezers to take a piece of WTe2 bulk material and place it on one side of the tape;
[0025] S12, stick the tape on the PDMS with the side of the WTe2 bulk material facing the PDMS on the glass slide, and press lightly to make the tape fit tightly with the PDMS; then lift one side of the tape and quickly peel off the tape from the PDMS, so that a thin layer of the WTe2 bulk material on the tape covers the surface of the PDMS; observe the glass slide and the PDMS as a whole under an optical microscope, and select a sample area with uniform thickness for preparing a suspended WTe2 film;
[0026] S14. Provide a silicon substrate with multiple holes with a diameter of 12μm, and use an inverted method to move the PDMS and glass slide covered with a WTe2 thin layer on the surface with the WTe2 thin layer facing downward and fit closely to the silicon substrate, so that the sample area selected by the WTe2 thin layer corresponds to the hole area of the silicon substrate. Heat the silicon substrate during the bonding process, and control the heating temperature at 105-115℃ for 8-12min. Then, cool it down to transfer the sample area selected by the WTe2 thin layer on the PDMS to the holes of the silicon substrate, thereby obtaining a suspended WTe2 film.
[0027] According to a preferred embodiment of the present invention, in S2, the method for determining the lattice orientation of the suspended WTe2 film is: calibrating the lattice orientation by angle-resolved Raman spectroscopy; or firstly performing a preliminary identification of the lattice direction by an optical image, and then further determining the lattice orientation by angle-resolved Raman spectroscopy. Among them, it can be observed through an optical microscope that the edge along the zigzag direction is longer and straighter than the armchair direction, so the lattice direction can be preliminarily identified based on its optical image.
[0028] According to a preferred embodiment of the present invention, in S2, a laser with an excitation wavelength is used, the polarization direction of the incident laser is parallel to the x-axis, the direction of the analyzer is the same as the polarization direction and remains unchanged, and the angular polarization Raman spectroscopy characteristics of the suspended WTe2 sample are tested, and the lattice orientation of the suspended WTe2 film is determined accordingly, which specifically includes the following steps:
[0029] (1) The laser incident direction and the direction of the analyzer are fixed on the x-axis and the sample is placed on the rotating sample stage; wherein the sample is initially placed in the zigzag direction preliminarily marked in the optical diagram and parallel to the x-axis, and the angle θ between the lattice direction of the sample and the laser incident direction is 0°;
[0030] (2) The rotating sample stage drives the sample to rotate clockwise around the z-axis at different angles so that the angle θ between the sample lattice direction and the laser incident direction varies between 0° and 360°, with a test interval of 10° to 20° (preferably 15°), and obtains the angular polarization Raman spectrum of the sample at different angles;
[0031] (3) The Raman characteristic peak intensity values corresponding to different angles θ are extracted and the polarization diagram is fitted. The lattice orientation of the sample is further analyzed through the polarization diagram.
[0032] According to a preferred embodiment of the present invention, in the process of analyzing according to the polarization diagram, the relationship between the Raman intensity of the A1 mode and the angle θ is analyzed according to the Placzek approximation method. The unit vector of the incident light in the parallel configuration is e i =(cosθ,sinθ,0), the unit vector of the scattered light is e s=(cosθ, sinθ, 0), so the relationship between the Raman peak intensity of the A1 mode and the angle θ is described by the following formula:
[0033]
[0034] where a and b are the elements of the Raman tensor that determine the Raman peak intensity;
[0035] When a > b, the maximum value of the Raman peak intensity of the A1 mode appears at θ = 0° and θ = 180°, that is, the polarization direction of the incident light is parallel to the metal atom W-W chain of the WTe2 material and corresponds to the zigzag direction; when a < b, the maximum Raman peak intensity of the A1 mode is located at θ = 90° and θ = 270°, and at this time the polarization direction of the incident light is perpendicular to the metal atom W-W chain of the WTe2 material and corresponds to the armchair direction.
[0036] According to a preferred embodiment of the present invention, in S2, it further includes characterizing the thickness and surface uniformity of the prepared suspended WTe2 thin film by an atomic force microscope.
[0037] According to a preferred embodiment of the present invention, in S3, Raman spectra are respectively tested at different temperatures along the zigzag direction and the armchair direction of the suspended WTe2 thin film, specifically including:
[0038] (1) First, perform a variable-temperature test on the suspended WTe2 thin film to calibrate the relationship between the Raman characteristic peak frequency and temperature, and calibrate the Raman spectrum;
[0039] During the variable-temperature test, place the suspended WTe2 thin film sample in the sample chamber and seal it, and then connect the sample chamber to the temperature controller and the liquid nitrogen tank; the controller controls the amount of liquid nitrogen input into the sample chamber by the liquid nitrogen tank for temperature control. After reaching the set temperature value and stabilizing for 3 - 5 minutes, perform Raman spectrum testing at the current temperature, so as to analyze the change of the Raman characteristic peak frequency of the suspended WTe2 thin film with temperature; during the test, the laser power is stable at ≤0.5 mW;
[0040] (2) Extract the 10 characteristic peak frequencies of the A1 Raman mode of the suspended WTe2 thin film at different temperatures for plotting, and analyze to obtain 10 the change curve of the characteristic peak frequency of the A1 Raman mode with temperature. Use formula I to fit this change curve, and after fitting, obtain 10 the first-order temperature coefficient χ of the A1 mode along the zigzag direction and the armchair direction T .
[0041] Among them, the Raman spectra at different temperatures are kept in a low-temperature liquid nitrogen environment for testing to avoid damage to the sample at high temperatures. During the Raman spectrum test, the laser power is kept within 0.5mW to avoid the laser causing the sample temperature to rise and affect the experimental results and analysis. -1 ( 4 A1)、163cm -1(8 A1) and 212cm -1 ( 10 In A1), 10 The A1 Raman characteristic peak is more sensitive to temperature, so in the following data extraction analysis, select 10 A1 Raman characteristic peak The change of the Raman characteristic peak frequency of WTe2 material is analyzed to calculate its thermal conductivity.
[0042] According to a preferred embodiment of the present invention, in S3, Raman spectroscopy is tested along the zigzag direction and the armchair direction of the suspended WTe2 film at different laser powers, that is, the sample is heated by the laser power to characterize the in-situ Raman spectrum of the suspended WTe2 film along the zigzag direction and the armchair direction at different laser powers, and the relationship between the Raman characteristic peak frequency and the laser power is determined; specifically including:
[0043] Step 1: The Raman laser spot is always focused on the central area of the suspended WTe2 film, which corresponds to the center of the hole on the silicon substrate. The Raman spectrum is detected by a laser of the excitation wavelength and a 50x objective lens with NA = 0.55. The laser spot is much smaller than the suspended area of the WTe2 film on the silicon substrate. The laser serves as a heating source for the sample and a detection laser for the Raman spectrum at the same time.
[0044] Step 2: Increase the incident laser power from 106μW to 325μW and extract the sample under different laser powers. 10 A1 Raman characteristic peak frequency is plotted along the zigzag direction and the armchair direction as the laser power changes. The Raman characteristic peak frequency and laser power change curve are analyzed, and the change curve is fitted using formula II. After fitting, the result is 10 The first-order power coefficient of A1 mode along the zigzag direction and armchair direction χ P .
[0045] In step 1, the laser spot diameter is only 616nm, which is much smaller than the suspended area of the WTe2 film on the silicon substrate (the diameter of the hole on the silicon substrate is 12μm). At this time, the heat transfer from the center of the suspended sample to the silicon substrate area at the edge of the hole can be ignored, which improves the detection accuracy. 10The change of A1 mode is more obvious, so the subsequent extraction of WTe2 film 10 The A1 Raman characteristic peak frequency is plotted as a function of laser power along the zigzag direction and the armchair direction.
[0046] According to a preferred embodiment of the present invention, in S4, the method for testing the absorbance of the sample along the zigzag direction and the armchair direction under the excitation laser wavelength is: under the laser of the excitation wavelength (consistent with the aforementioned Raman detection laser wavelength, usually 532nm), fix the laser incident direction, rotate the suspended WTe2 film from 0° to 90°, and test the change trend of its absorbance value in different directions; here 0° corresponds to the zigzag direction of the sample, and 90° corresponds to the armchair direction of the sample.
[0047] According to a preferred embodiment of the present invention, when the excitation wavelength of the Raman spectrum test laser is 532 nm, the absorption rates of the suspended WTe2 film along the zigzag direction and the armchair direction are 55%±0.10% and 54%±0.10%, respectively.
[0048] The first-order temperature coefficient χ obtained in S3 and S4 T , first-order power coefficient χ P、 Substituting the absorptivity of the sample along the zigzag direction and the armchair direction at the excitation laser wavelength, the sample thickness h, etc. into Formula III, the in-plane thermal conductivity of the sample along the zigzag direction and the armchair direction can be obtained. The ratio of the in-plane thermal conductivity along the zigzag direction to the in-plane thermal conductivity in the armchair direction is calculated to obtain the thermal transport anisotropy ratio.
[0049] (III) Beneficial effects
[0050] The present invention prepares a suspended WTe2 film and calibrates its lattice orientation through angle-resolved Raman spectroscopy based on its low-symmetric lattice structure, and performs optical heating Raman tests and absorptivity tests at variable temperatures and laser powers along different lattice directions, and calculates the in-plane thermal conductivity and heat transport anisotropy ratio of the suspended WTe2 film along the zigzag direction and the armchair direction. After analysis, it is found that the in-plane thermal conductivity of the suspended WTe2 film along the zigzag direction and the armchair direction is 4.45 Wm -1 .K -1 and 4.10Wm -1 .K -1, which shows obvious thermal transport anisotropy, and the thermal transport anisotropy ratio is about 1.09. The analysis of the anisotropic thermal transport characteristics of the suspended WTe2 film by the method of the present invention can provide reference and guidance for the structural design, performance optimization and heat dissipation regulation and management of WTe2 functional devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 This is the low-symmetry lattice structure of WTe2, with blue representing metal atoms W and gray representing Te.
[0052] Figure 2 This is a method for preparing suspended WTe2 thin film samples by mechanical exfoliation.
[0053] Figure 3 It is a suspended WTe2 film located in the hole area on the silicon substrate.
[0054] Figure 4 AFM image of a suspended WTe2 film in the hole region on a silicon substrate.
[0055] Figure 5 Angular polarization Raman spectra of suspended WTe2 films at different angles. (a) Angular polarization Raman spectra of suspended WTe2 films at different angles. 4 A1. 8 A1 and 10 A1 is the trend diagram of the change of Raman characteristic peak intensity; (b), (c), and (d) are the detailed enlarged diagrams of the change of the intensity of the three Raman characteristic peaks with angle.
[0056] Figure 6 Color images of the angle-resolved Raman spectra of suspended WTe2 films at different angles.
[0057] Figure 7 Polarization diagram of the Raman characteristic peak intensity change of the suspended WTe2 film at different angles; (a) 3 Polarization diagram of the intensity of the A2 Raman characteristic peak as a function of angle; (b), (c) and (d) are 4 A1. 8 A1. 10 Polarization diagram of A1 Raman characteristic peak intensity varying with angle.
[0058] Figure 8 Schematic diagram of the Raman variable temperature test device.
[0059] Fig. 9 Figure 2 shows the (a) zigzag direction and (b) armchair direction of the suspended WTe2 film at different temperatures. 8 A1 and 10 A1 Raman characteristic peak frequency change trend diagram.
[0060] Fig.10 Figure 2 shows the (a) zigzag direction and (b) armchair direction of the suspended WTe2 film. 10 Linear fitting diagram of the relationship between A1 Raman characteristic peak frequency and temperature change, first-order temperature coefficient χ T -0.0177cm -1 .K -1 and 0.0126cm - 1 .K -1 .
[0061] Fig.11 Schematic diagram of the photo-heated Raman temperature measurement device.
[0062] Fig.12 Figure 3 shows the (a) zigzag direction and (b) armchair direction of the suspended WTe2 film under different laser powers. 8 A1 and 10 A1 Raman characteristic peak frequency change trend diagram.
[0063] Fig.13 The (a) zigzag direction and (b) armchair direction of the suspended WTe2 film 10 Linear fitting diagram of the relationship between A1 Raman characteristic peak frequency and laser power change, first-order power coefficient χ P -0.0069cm respectively -1 .μW -1 and -0.0053cm -1 .μW -1 .
[0064] Fig.14 When the laser incident direction is fixed on the x-axis, the absorptivity of the suspended WTe2 film rotated from 0° to 90°.
[0065] Fig.15 Comparison of the in-plane thermal conductivity of suspended WTe2 films along the zigzag direction and the armchair direction; the horizontal axis in the figure is the lattice direction of the sample, and the vertical axis is the in-plane thermal conductivity value. DETAILED DESCRIPTION
[0066] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.
[0067] The present invention provides a method for analyzing the anisotropic thermal transport characteristics of a suspended WTe2 film, which includes the following parts, which are described in detail below in conjunction with the accompanying drawings.
[0068] (i) Providing a suspended WTe2 film; the suspended WTe2 film is a structure formed by the WTe2 film covering the hole area on the silicon substrate.
[0069] The present invention adopts a mechanical stripping method to separate the bulk material to prepare a suspended WTe2 film. During the preparation process, the WTe2 bulk material is mechanically stripped by tape to obtain a WTe2 film on polydimethylsiloxane (PDMS), and then it is dry-transferred to a silicon substrate with holes (a plurality of holes with a diameter of 12 μm are etched on the silicon substrate), so that the WTe2 film covers the holes, thereby forming a suspended WTe2 film area on the silicon wafer.
[0070] The detailed process of preparing suspended WTe2 thin film samples can be found in Figure 2 :
[0071] (1) Take a clean glass slide and wipe off the debris on its surface with alcohol, cut a piece of PDMS of any size and stick it to the middle of the glass slide, and set it aside for later use; (2) Cut a clean blue tape, use tweezers to take a piece of WTe2 block material and place it on one side of the tape, and fold it repeatedly until the area of the WTe2 block distributed on the tape is close to the size of the spare PDMS ( Figure 2 a); (3) gently stick the tape on the prepared PDMS / glass slide and gently press to make the tape and PDMS fit as closely as possible ( Figure 2 b); (4) After close fitting, lift one side of the tape and quickly and completely peel it off from the PDMS / glass slide so that the WTe2 material on the tape covers the surface of the PDMS ( Figure 2 c); (5) Place the PDMS / glass slide under an optical microscope for observation, and select a sample area with uniform thickness and appropriate size for subsequent dry transfer to prepare a suspended WTe2 film on the holes of the silicon substrate (multiple holes with a diameter of 12 μm were etched on the silicon substrate) Figure 2 d).
[0072] The process of dry transfer is as follows: cut a piece of PDMS with the same size as the transfer table, stick it on the central area of the transfer table, stick the silicon substrate on the PDMS, and fix the silicon substrate on the transfer table with the help of PDMS; under a microscope, use alcohol to clean the holes and edges on the silicon substrate; fix the PDMS and the glass slide covered with a thin layer of WTe2 on the surface with the WTe2 thin layer facing down on the clamping table (that is, the order from top to bottom is: glass slide / PDMS / WTe2), and find the selected sample area under the microscope; adjust the position of the entire transfer table to align the holes on the silicon substrate with the selected sample area; manually lower the clamping table to make the PDMS close to the silicon substrate, and at the same time turn on the heating table to heat the transfer table carrying the silicon substrate to 60℃ (55-65℃); continue to manually lower the clamping table, observe the descending progress with a microscope during the descending process, stop manual descending when the PDMS is close to the hole area on the silicon substrate, heat the transfer table in steps of 0.1℃ to make the PDMS under the silicon substrate expand and push up the silicon substrate, so that it naturally fits with the PDMS above; when the WTe2 thin layer on the PDMS completely covers the holes in the silicon substrate, increase the heating rate, heat the transfer table to about 110℃ (105-115℃) to continue to increase the fit, and keep it warm for about 10min (8-12min); after the insulation is completed, lower the temperature to allow the transfer table to cool down slowly (PDMS shrinks) until the upper glass slide / PDMS is completely separated from the lower silicon substrate. At this time, the selected sample area of the WTe2 thin layer on the PMDS on the clamping stage is transferred to the hole area on the silicon substrate, thereby obtaining a suspended WTe2 thin film, and the prepared suspended WTe2 thin film is subjected to subsequent morphological characterization and thermal transport performance testing.
[0073] According to the above method, we can obtain Figure 3 The suspended WTe2 film in the hole area on the silicon substrate is shown. The red circle in the figure is the suspended area; the hole diameter is 12μm; the scale bar of the picture is 20μm. Figure 3 It can be seen that the coverage of the WTe2 film is much larger than the hole size, so as to obtain the suspended WTe2 film area. Since the dissociation energy in the zigzag direction is smaller than that in the armchair direction, the WTe2 material is more likely to break along the zigzag direction during mechanical stripping, which can be used to preliminarily judge its lattice direction. Figure 3 The coordinate system in the lower left corner defines the horizontal x-axis as the zigzag direction and the y-axis as the armchair direction.
[0074] (ii) The thickness and surface uniformity of the suspended WTe2 film were characterized by atomic force microscopy, and the lattice orientation was further determined by angle-resolved Raman spectroscopy.
[0075] After the preparation of the suspended WTe2 film sample was completed, the thickness and surface uniformity of the suspended WTe2 film were further characterized by atomic force microscopy (AFM) in tapping mode (mainly characterizing the morphology of the WTe2 material in the center of the pore area). Figure 4 It can be seen from the height curve in that the thickness of the suspended WTe2 film selected here is about 50nm, and the morphology diagram shows that the thickness of the WTe2 material is relatively uniform and can completely cover the holes in the silicon wafer. Figure 4 This is an AFM image of a suspended WTe2 film in the hole area on a silicon substrate; the small inset in the upper right corner is the height curve of the suspended WTe2 sample, which is approximately 50nm thick; the scale of the image is 5μm.
[0076] In addition, the prepared samples can be observed under an optical microscope. WTe2 regions with different optical contrasts correspond to different sample thicknesses, and the sample regions can be observed to be relatively flat. It can be seen that this stripping method can separate WTe2 bulk materials into thin films with atomic-level thickness, relatively flat surface, few defects and high mobility.
[0077] Next, it is necessary to characterize its optical anisotropy and further calibrate its lattice orientation through angle-resolved Raman spectroscopy testing, so as to facilitate the subsequent testing of thermal transport performance along different lattice directions. Specifically, a rotatable sample stage is placed on the Raman spectrometer, and the sample is placed at the center of the rotating stage. The angle θ between the lattice direction of the sample and the laser incident direction is changed by rotating the sample stage, and the Raman spectrum is tested at different angles θ. The law of how the intensity of the Raman characteristic peak of the WTe2 material changes with the angle is analyzed by formula to determine its lattice direction. During the test, a laser with an excitation wavelength of 532nm is used so that the polarization direction of the incident laser and the direction of the analyzer are parallel to the x-axis and remain unchanged, that is, the angular polarization Raman spectral characteristics of the suspended WTe2 sample are always analyzed in a parallel configuration. The test process is as follows:
[0078] (1) Figure 3 The zigzag direction preliminarily marked in the figure is placed horizontally (parallel to the x-axis) at the center of the rotatable sample stage, and the angle θ at this time is defined as the initial 0°. The sample is rotated clockwise by adjusting the sample stage to change the angle θ between the WTe2 lattice direction and the incident laser direction (the range of θ is 0°-360°, and the test interval angle is 15°) to obtain the Raman spectrum of the suspended WTe2 film at different angles. Figure 5 The Raman spectra of some bands corresponding to different angles θ, the angle in the figure is the angle between the sample lattice direction and the laser incident direction (the range is 0°-360°), and the Raman peak intensity of the suspended WTe2 film changes with the angle. Figure 5(a) is at different angles 4 A1. 8 A1 and 10 A1 Raman characteristic peak intensity variation trend diagram; Figure (b)-(d) is 133cm -1 ( 4 A1)、163cm -1 ( 8 A1) and 212cm -1 ( 10 A1) Detailed magnification of the Raman spectra of the three main A1 modes at different angles θ.
[0079] (2) In order to more clearly observe the change of Raman peak intensity with angle, the Raman characteristic peak intensity values of the suspended WTe2 film corresponding to different angles were extracted, and the relationship between the Raman characteristic peak intensity and the angle was plotted. The polarization diagram was fitted from this relationship diagram, and the lattice orientation of the sample was further analyzed through the polarization diagram.
[0080] like Figure 6 As shown in the figure, it is a color map of the angle-resolved Raman spectrum of the suspended WTe2 film at different angles. The red part in the figure represents the area with the maximum peak intensity, and the blue part represents the area with the minimum peak intensity. It can be seen that the Raman characteristic peak intensity shows a periodic change law with the change of angle, and the polarization diagram is fitted. The periodic law of the peak intensity changing with the angle is explored through the polarization diagram. Specifically, in the process of analyzing according to the polarization diagram, the relationship between the Raman intensity of the A1 and A2 modes and the angle θ can also be analyzed in combination with the Placzek approximation method, and the analysis results of the Placzek approximation method and the polarization diagram are mutually verified. As the angle θ changes from 0° to 360°, the change in the Raman intensity of the A1 and A2 modes can be described by the following formula:
[0081]
[0082] is the Raman tensor, In the parallel configuration, the unit vector of the incident light is e i =(cosθ, sinθ, 0), the unit vector of the scattered light is e s =(cosθ, sinθ, 0). Therefore, after substituting it into formula (1-1), the relationship between the Raman peak intensity of A1 and A2 modes and the angle θ can be described as:
[0083]
[0084] where a, b and d are the elements of the Raman tensor that determine the intensity of the Raman peak.
[0085] According to formulas (1-2) and (1-3), it can be seen that the intensity variation law of the A2-mode Raman characteristic peak of the suspended WTe2 film shows four-fold symmetry with respect to the angle, while the intensity variation law of the A1-mode Raman characteristic peak shows two-fold symmetry with respect to the angle, which is consistent with Figure 7 the experimental results of the polarization diagrams drawn. At the same time, from formula (1-2), it can be seen that the variation law of the Raman peak intensity of the A1 mode is also related to the relationship between the Raman tensor elements a and b. When a > b, the maximum value of the Raman peak intensity of the A1 mode appears at θ = 0° and θ = 180°, that is, the polarization direction of the incident light is parallel to the metal atom W-W chain of the WTe2 material (corresponding to the zigzag direction), as 4 A1 and 8 the polarization directions of the A1 mode; when a < b, the maximum Raman peak intensity of the A1 mode is located at θ = 90° and θ = 270°, and at this time the polarization direction of the incident light is perpendicular to the metal atom W-W chain of the WTe2 material (corresponding to the armchair direction), as 10 the polarization direction of the A1 mode is consistent with Figure 3 the preliminary judgment of the lattice orientation in
[0086] (3) Raman spectra were measured along the zigzag direction and the armchair direction of the suspended WTe2 film at different temperatures and different laser powers, and the variation laws of the Raman characteristic peak frequencies with temperature and laser power were analyzed. The first-order temperature coefficient χT and the first-order power coefficient χ P of the suspended WTe2 film along the zigzag direction and the armchair direction were calculated by substituting them into the corresponding relational formulas I and II respectively.
[0087] First step, first perform a temperature-variable test on the suspended WTe2 film to calibrate the relationship between its Raman characteristic peak frequency and temperature, and calibrate the Raman spectrum. During the temperature-variable test, the sample was placed in the sample chamber of the temperature-variable test device as Figure 8 shown and sealed, and then the sample chamber was connected to the temperature controller and the liquid nitrogen tank. The temperature controller was adjusted to set the temperature of the sample chamber, that is, the amount of liquid nitrogen introduced into the sample chamber was adjusted for temperature control. After the temperature reading on the temperature controller reached the set value and stabilized for 3 - 5 minutes, the Raman spectrum was measured at the current temperature, so as to analyze the variation of the Raman characteristic peak frequency of the suspended WTe2 film with temperature. In order to avoid damaging the sample at higher temperatures, the Raman spectra at different temperatures were all measured in a low-temperature liquid nitrogen environment. In addition, during the Raman spectrum measurement process, the laser power was kept within 0.5 mW to avoid the laser causing the sample temperature to rise and affecting the analysis of the experimental results. As Figure 8 shown, for the suspended WTe2 film 8 A1 (located at 163 cm -1 ) and10 A1(212cm -1 )The peak position of the Raman mode changes with temperature (the temperature range of the variable temperature test here is 203K to 273K, with a temperature interval of 10K). Fig. 9 It can be seen that with the increase of temperature, 8 A1 and 10 The Raman peak position of the A1 mode has obviously moved toward the low frequency direction, which is called red shift. This red shift phenomenon is caused by the non-harmonic lattice vibration and thermal expansion caused by temperature change. It can also be observed from the figure that 8 A1 and 10 The red shift of the A1 Raman characteristic peak frequency is significantly different as the temperature increases. When the temperature changes from 203K to 273K, 8 The A1 Raman characteristic peak frequency is red-shifted by about 0.9 and 0.7 wavenumbers along the zigzag and armchair directions, respectively. 10 The A1 Raman characteristic peak frequency red-shifted by 1.2 and 0.8 wavenumbers along the zigzag and armchair directions, respectively; this research conclusion shows that 10 The A1 Raman characteristic peak is more sensitive to temperature. Therefore, in the following data extraction and analysis, we choose 10 The A1 Raman characteristic peak is used as the Raman characteristic peak frequency of WTe2 material to analyze the change of temperature to calculate its thermal conductivity.
[0088] Furthermore, the suspended WTe2 films at different temperatures were extracted. 10 The characteristic peak frequency of A1 Raman mode is plotted, the relationship between Raman characteristic peak frequency and temperature change is analyzed, and its Raman spectrum is calibrated, such as Fig.10 It shows that as the temperature increases, 10 The peak position of the A1 Raman characteristic peak along the zigzag direction and the armchair direction shows a linear red shift trend, with a red shift of 1.2 wave numbers along the zigzag direction and a red shift of 0.8 wave numbers along the armchair direction. 10 The A1 Raman characteristic peak frequency and temperature change curve are fitted, and the fitting results are 10 The first-order temperature coefficients of the A1 mode along the zigzag and armchair directions χ T (Represents the relationship between the Raman characteristic peak frequency and temperature of the suspended WTe2 film), where the zigzag direction is -0.0177±0.0008cm -1 .K -1 , armchair direction is -0.0126±0.0004cm -1 .K -1, showing obvious anisotropy. The relationship between the Raman characteristic peak frequency and temperature is as follows:
[0089] ω=ω0+χ T T(Formula I)
[0090] Where ω0 is the Raman characteristic peak frequency of the sample at 0K, T is the actual temperature at that time, and χ T The corresponding first-order temperature coefficient is the relationship between the Raman characteristic peak frequency of the material and temperature.
[0091] For WTe2 materials with directional differences in lattice structure, its first-order temperature coefficient χ T The difference between the zigzag direction and the armchair direction is caused by the difference in the phonon group velocity and the mean free path in the zigzag and armchair directions.
[0092] The second step is to conduct a variable laser power test of the Raman temperature measurement method, that is, to heat the material through the laser power to characterize the in-situ Raman spectrum of the suspended WTe2 film along the zigzag direction and the armchair direction at different laser powers, and to determine the relationship between the Raman characteristic peak frequency and the laser power. During the test, the Raman laser spot is always focused on the central area of the suspended WTe2 film (that is, the center of the silicon substrate hole of the suspended WTe2 film), and the Raman spectrum is detected by a laser with an excitation wavelength of 532nm and a 50x (NA=0.55) objective lens. The size of the laser spot (the laser spot diameter is 616nm) is much smaller than the suspended area of the WTe2 film on the silicon substrate (the diameter of the hole on the silicon substrate is 12μm), that is, the heat transfer from the center of the suspended sample to the substrate area at the edge of the hole is negligible. Fig.11 The figure shows a schematic diagram of a light-heating Raman temperature measurement device, in which the laser is used as both the heating source of the sample and the detection laser of its Raman spectrum.
[0093] like Fig.12 As shown in Figure 2, the Raman spectrum of the suspended WTe2 film is increased when the incident laser power increases from 106μW to 325μW. As the laser power increases, the temperature of the area of the suspended WTe2 film irradiated by the laser increases. 8 A1 and 10 The frequencies of the A1 Raman characteristic peaks all show a red shift phenomenon moving toward the low frequency direction. 8 The A1 Raman characteristic peak frequency red-shifted by 0.8 wavenumbers, while 10 The A1 Raman characteristic peak frequency is red-shifted by 1.4 wavenumbers. As mentioned above, the same laser power range causes 8 A1 and 10The change in the frequency of the A1 Raman characteristic peak is different, and 10 The Raman characteristic peak of A1 mode changes more obviously.
[0094] Further analysis of the suspended WTe2 film under different laser powers 10 The A1 Raman peak frequency changes along the zigzag direction and the armchair direction, and the relationship between the Raman characteristic peak frequency and the laser power is analyzed. The relationship diagram shows that as the laser power increases, 10 The A1 Raman peak frequency undergoes a linear red shift along both the zigzag and armchair directions, with a red shift of 1.4 wave numbers along the zigzag direction and a red shift of 1.1 wave numbers along the armchair direction. The relationship between the Raman characteristic peak frequency and the laser power is fitted using the linear relationship formula (Formula II) of the Raman characteristic peak frequency and power, and the following is obtained: Fig.13 The linear fitting diagram is shown in the figure, where the first-order power coefficient of the suspended WTe2 film along the zigzag direction and the armchair direction is χ P (representing the relationship between the Raman characteristic peak frequency of the suspended WTe2 film and the laser power) are -0.0069±0.0002cm -1 .μW -1 and -0.0053±0.0001cm -1 .μW -1 , that is, the zigzag direction is more sensitive to laser power than the armchair direction, showing a more obvious redshift phenomenon.
[0095] The linear relationship between the frequency of the above Raman characteristic peak and the power is as follows:
[0096] Δω=ω(P2)-ω(P1)=χ P (P2-P1)=χ P ΔP (Formula II)
[0097] Among them, P is the laser power, Δω is the change in Raman characteristic peak frequency caused by the power increasing from P1 to P2, and χP is the first-order power coefficient, that is, the relationship between the Raman characteristic frequency of the material and the power.
[0098] (iv) Test the sample's absorbance along the zigzag direction and the armchair direction at the excitation laser wavelength, and then calculate the in-plane thermal conductivity and thermal transport anisotropy ratio of the suspended WTe2 film along the zigzag direction and the armchair direction according to Formula III in combination with the sample thickness h;
[0099] The in-plane thermal conductivity κ of the suspended WTe2 thin film sample is calculated as follows:
[0100] κ=χ T (1 / 2πh)(δω / δP A ) -1 Formula (III);
[0101] Thermal transport anisotropy ratio = κ zigzag / κa rmchair ;
[0102] Where h is the thickness of the sample, δω is the absorption of δP by the sample. A The change in the characteristic peak frequency after the power is A is the absorbed power of the sample, P A =AP, P is the laser power, and A is the absorbance value of the sample at the test laser wavelength.
[0103] The method for testing the absorbance of the sample along the zigzag direction and the armchair direction under the excitation laser wavelength is as follows: at a laser wavelength of 532nm, fix the laser incident direction, rotate the suspended WTe2 film from 0° to 90°, and test the change trend of the absorbance value in different directions (such as Fig.14 As shown). According to the above analysis of the diagonally polarized Raman spectrum, 0° here corresponds to the zigzag direction of the sample, and 90° corresponds to the armchair direction of the sample. The specific data were read, and the absorption rates of the suspended WTe2 film along the zigzag direction and the armchair direction were 55% and 54%, respectively. In addition, considering the Poisson distribution of the continuous and stable number of photons during the test, as well as the influence of the noise and dark current read by the CCD on the experimental data, the error range of the experimental test is about 0.10%. Therefore, at a laser wavelength of 532nm, the absorption rates of the suspended WTe2 film along the zigzag direction and the armchair direction are 55%±0.10% and 54%±0.10%, respectively.
[0104] The thickness h and the first-order temperature coefficient χ in different directions obtained from the above test are T , first-order power coefficient χ p , and the absorption rate values are substituted into Formula III respectively to calculate the in-plane thermal conductivity values of the suspended WTe2 film along different lattice directions.
[0105] like Fig.15 As shown in Figure 2, the in-plane thermal conductivity of the suspended WTe2 film along the zigzag direction and the armchair direction is 4.45 Wm -1 .K -1 and 4.10Wm -1 .K -1 The suspended WTe2 thin film samples show obvious directional differences, and the thermal transport anisotropy ratio (k zigzag / karmchair ) is about 1.09. This anisotropy of heat transport performance can be attributed to the difference in group velocity of the acoustic modes, that is, the group velocity along the zigzag direction is greater than the velocity along the armchair direction.
[0106] The anisotropic thermal transport characteristics of suspended WTe2 thin films are analyzed by the method of the present invention, which can provide reference and guidance for the structural design, performance optimization and regulation and management of heat dissipation of WTe2 functional devices.
[0107] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for analyzing the anisotropic thermal transport properties of a suspended WTe2 film, characterized in that: The steps include: S1, providing a suspended WTe2 film; the suspended WTe2 film is a structure formed by the WTe2 film covering the hole area on the silicon substrate; S2, determine the lattice orientation of the suspended WTe2 film; S3. Raman spectra were tested along the zigzag direction and armchair direction of the suspended WTe2 film at different temperatures and different laser powers. The variation of the Raman characteristic peak frequency with temperature and laser power was analyzed. The first-order temperature coefficient χ of the suspended WTe2 film along the zigzag direction and armchair direction was calculated by substituting the corresponding relationship formula I and formula II. T and the first-order power coefficient χ P ; Among them, the relationship between the Raman characteristic peak frequency and temperature is as follows: ω=ω0+χ T Formula I Where ω0 is the Raman characteristic peak frequency of the sample at 0K, T is the actual temperature at that time, and χ T The corresponding first-order temperature coefficient is the relationship between the Raman characteristic peak frequency of the material and temperature; The linear relationship between Raman characteristic peak frequency and power is as follows: Dω=ω(P2)-ω(P1)=x P (P2-P1)=x P ΔP formula II Where P is the laser power, Δω is the change in Raman characteristic peak frequency caused by the power increasing from P1 to P2, and χ P It is the first-order power coefficient, i.e. the relationship between the Raman characteristic frequency and power of the material; S4. The absorbance of the test sample along the zigzag direction and the armchair direction at the excitation laser wavelength is calculated according to formula III based on the sample thickness h and the in-plane thermal conductivity and thermal transport anisotropy ratio of the suspended WTe2 film along the zigzag direction and the armchair direction; The in-plane thermal conductivity κ of the suspended WTe2 thin film sample is calculated as follows: κ = χ T (1 / 2πh)(δω / δP A ) -1 Formula III; Thermal transport anisotropy ratio = κ zigzag / κa rmchair ; Where h is the thickness of the sample, δω is the absorption of δP by the sample. A The change in the characteristic peak frequency after the power is A is the absorbed power of the sample, P A =AP, P is the laser power, and A is the absorbance value of the sample at the test laser wavelength.
2. The analysis method according to claim 1, characterized in that In S1, the preparation method of the suspended WTe2 film is: S11. Take a clean glass slide and wipe it with alcohol, cut a piece of PDMS and stick it on the glass slide for later use; cut a clean tape, use tweezers to take a piece of WTe2 bulk material and place it on one side of the tape; S12, stick the tape on the PDMS with the side of the WTe2 bulk material facing the PDMS on the glass slide, and press lightly to make the tape fit tightly with the PDMS; then lift one side of the tape and quickly peel off the tape from the PDMS, so that a thin layer of the WTe2 bulk material on the tape covers the surface of the PDMS; observe the glass slide and the PDMS as a whole under an optical microscope, and select a sample area with uniform thickness for preparing a suspended WTe2 film; S14. Provide a silicon substrate with multiple holes with a diameter of 12μm, and use an inverted method to move the PDMS and glass slide covered with a WTe2 thin layer on the surface with the WTe2 thin layer facing downward and fit closely to the silicon substrate, so that the sample area selected by the WTe2 thin layer corresponds to the hole area of the silicon substrate. Heat the silicon substrate during the bonding process, and control the heating temperature at 105-115℃ for 8-12min. Then, cool it down to transfer the sample area selected by the WTe2 thin layer on the PDMS to the holes of the silicon substrate, thereby obtaining a suspended WTe2 film.
3. The analysis method according to claim 2, characterized in that In S2, the method for determining the lattice orientation of the suspended WTe2 film is: calibrating the lattice orientation through angle-resolved Raman spectroscopy; or, first preliminarily identifying the lattice direction through an optical image, and then further determining the lattice orientation with the help of angle-resolved Raman spectroscopy.
4. The analysis method according to claim 2, characterized in that In S2, a laser with an excitation wavelength is used to make the polarization direction of the incident laser parallel to the x-axis. The direction of the analyzer is the same as the polarization direction and remains unchanged. The angular polarization Raman spectroscopy characteristics of the suspended WTe2 sample are tested, and the lattice orientation of the suspended WTe2 film is determined accordingly. Specifically, the following steps are included: (1) The laser incident direction and the direction of the analyzer are fixed on the x-axis and the sample is placed on the rotating sample stage; wherein the sample is initially placed in the zigzag direction preliminarily marked in the optical diagram and parallel to the x-axis, and the angle θ between the lattice direction of the sample and the laser incident direction is 0°; (2) The rotating sample stage drives the sample to rotate clockwise around the z-axis by different angles, so that the angle θ between the sample lattice direction and the laser incident direction varies between 0° and 360°, and the test interval is 10 - 20°. In this way, the angular polarization Raman spectra of the sample at different angles are obtained; (3) Extract the Raman characteristic peak intensity values corresponding to different angles θ, fit the polarization diagram, and further analyze the polarization diagram to obtain the lattice orientation of the sample.
5. The analysis method according to claim 4, characterized in that In the process of analyzing the polarization diagram, the relationship between the Raman intensity of the A1 mode and the angle θ is analyzed according to the Placzek approximation method. The unit vector of the incident light in the parallel configuration is e i =(cosθ,sinθ,0), the unit vector of the scattered light is e s =(cosθ, sinθ, 0), so the relationship between the Raman peak intensity of the A1 mode and the angle θ is described by the following formula: Among them, a and b are the elements of the Raman tensor that determine the Raman peak intensity; When a > b, the maximum value of the Raman peak intensity of the A1 mode appears at θ = 0° and θ = 180°, that is, the polarization direction of the incident light is parallel to the metal atom W-W chain of the WTe2 material and corresponds to the zigzag direction; when a < b, the maximum Raman peak intensity of the A1 mode is located at θ = 90° and θ = 270°, and at this time the polarization direction of the incident light is perpendicular to the metal atom W-W chain of the WTe2 material and corresponds to the armchair direction.
6. The analysis method according to claim 2, characterized in that In S2, it also includes characterizing the thickness and surface uniformity of the prepared suspended WTe2 thin film by atomic force microscopy.
7. The analysis method according to claim 2, characterized in that In S3, Raman spectra are measured along the zigzag direction and the armchair direction of the suspended WTe2 thin film at different temperatures, specifically including: (1) First, perform a variable-temperature test on the suspended WTe2 thin film, calibrate the relationship between the Raman characteristic peak frequency and temperature, and calibrate the Raman spectrum; During the variable-temperature test, place the suspended WTe2 thin film sample in the sample chamber and seal it, then connect the sample chamber to the temperature controller and the liquid nitrogen tank; the controller controls the amount of liquid nitrogen input into the sample chamber by the liquid nitrogen tank for temperature control. After reaching the set temperature value and stabilizing for 3 - 5 minutes, measure the Raman spectrum at the current temperature, so as to analyze the change of the Raman characteristic peak frequency of the suspended WTe2 thin film with temperature; during the test, the laser power is stable at ≤0.5 mW; (2) Extraction of suspended WTe2 films at different temperatures 10 The characteristic peak frequency of A1 Raman mode is plotted and analyzed to obtain 10 A1 Raman mode characteristic peak frequency and temperature change curve, the change curve is fitted using formula I, and the fitting result is 10 The first-order temperature coefficient χT of the A1 mode along the zigzag and armchair directions.
8. The analysis method according to claim 2, characterized in that In S3, Raman spectra are measured along the zigzag direction and the armchair direction of the suspended WTe2 thin film at different laser powers, that is, the sample is heated by the laser power to characterize the in-situ Raman spectra of the suspended WTe2 thin film along the zigzag direction and the armchair direction at different laser powers, and determine the relationship between the Raman characteristic peak frequency and the laser power; specifically including: Step 1: Always focus the Raman laser spot on the central region of the suspended WTe2 thin film, that is, the center of the hole corresponding to the silicon substrate. The Raman spectrum is detected by a laser with an excitation wavelength and an objective lens with a magnification of 50 times and NA = 0.
55. The laser spot is much smaller than the suspended area of the WTe2 thin film on the silicon substrate, and the laser serves as both the heating source of the sample and the detection laser for the Raman spectrum; Step 2: Increase the incident laser power from 106μW to 325μW and extract the sample under different laser powers. 10 A1 Raman characteristic peak frequency is plotted along the zigzag direction and the armchair direction as the laser power changes. The Raman characteristic peak frequency and laser power change curve are analyzed, and the change curve is fitted using formula II. After fitting, the result is 10 The first-order power coefficient of A1 mode along the zigzag direction and armchair direction χ P .
9. The analysis method according to claim 2, characterized in that In S4, the method for testing the absorbance of the sample along the zigzag direction and the armchair direction under the excitation laser wavelength is as follows: under the laser of the excitation wavelength, fix the laser incident direction, rotate the suspended WTe2 film from 0° to 90°, and test the change trend of its absorbance value in different directions; here 0° corresponds to the zigzag direction of the sample, and 90° corresponds to the armchair direction of the sample.
10. The analysis method according to claim 1, characterized in that The excitation wavelength of the Raman spectroscopy test laser is 532nm, and the absorption rates of the suspended WTe2 film along the zigzag direction and the armchair direction are 55%±0.10% and 54%±0.10%, respectively.
Citation Information
Patent Citations
Method for measuring thermal conductivity of thin film based on fluorescent micro-nano-particles
CN107102026A
Low-dimensional material heat conductivity test method and test system
CN111103318A
Preparation method of one-dimensional platinum diselenide nanobelt and prepared platinum diselenide nanobelt
CN113948612A
Method for rapidly judging crystal lattice direction of purple phosphorus block and application of method
CN115308191A
Method and apparatus for measuring orientation of crystal
JP1997257692A